Smart Home Automation Based On Bluetooth with IR Receiver - Al-Fahdi, Juhina Abdullah; Al-Yahyaai, Hajar Fadhil; Al-Rashdi, Bayan Rashid; Muthu, Annamalai (International Journal of Scientific Research in Computer Science and Engineering, 2022)
The safety and happiness of life at home are ensured by the current home automation system. As a result, the adoption of home automation technologies is growing in popularity, and as the saying goes, as technology advances, so do homes. Energy conservation is therefore more crucial than ever due to increased energy usage and population. The inability to handle equipment from remote locations is one of the major reasons of energy waste. Thus, by creating the Arduino UNO, the ATMEL has been able to advance Arduino in recent years. Here, we present a really intriguing concept: utilizing an Android application and Bluetooth, users may operate home appliances from distant locations. The basic goal is to build a Bluetooth-enabled, Arduino-powered home automation system that can be operated remotely by any Android smartphone. Therefore, we create an Arduino-based Bluetooth module that includes an IR receiver, a relay module, a Bluetooth module, and manual control switches to control home appliances. Through the Bluetooth module, the Arduino receives data from the smartphone. In order to operate the home appliances, the Arduino will then send a signal to the relay module. Both the manual switches and the IR remote control can be used to control the devices and turn on and off household appliances. This module is simple to use and makes it simple to utilize your home appliances.